Follicular occlusion tetrad in a male patient with pachyonychia congenita: clinical and genetic analysis. (19th September 2019) - Musumeci, M.L.; Fiorentini, F.; Bianchi, L.; Cascella, R.; Giardina, E.; Caputo, V.; Micali, G.
Abstract: The case of a 24‐year‐old male patient affected by follicular occlusion tetrad (acne conglobata, hidradenitis suppurativa, pilonidal cyst and dissecting cellulitis of the scalp) associated with clinical signs of pachyonychia congenita (PC)‐2 (focal palmoplantar keratoderma, plantar pain, onycodystrophy and multiple cysts) is reported. The diagnosis was supported by genetic analysis that showed heterozygous mutation within the exon 1 of KRT17 gene. This case may reflect different expressions of a phenotypic spectrum induced by a common genetic alteration.